Imaging Outcomes of MRI After CT in Pediatric Spinal Trauma : A Single-center Experience - Sirén, Aapo; Nyman, Mikko; Syvänen, Johanna; Mattila, Kimmo; Hirvonen, Jussi (Lippincott, 2025)
ackground:
Imaging has an essential role in the diagnostic workup of suspected pediatric spinal trauma. The most suitable imaging method is still being debated and needs to be considered regarding the patient, injury, and local resources. Magnetic resonance imaging (MRI) is often performed after computed tomography (CT) in case of neurological symptoms or suspected ligamentous disruption. However, it is unclear if the MRI yields significant additional value after CT if the spinal cord injury is not suspected and if the MRI could be used as the sole imaging modality in an emergency department. This study aimed to assess the diagnostic value of emergency MRI after CT in suspected spinal trauma in children and adolescents.
Methods:
The imaging data and medical records of patients 17 years of age and younger with emergency spinal CT and MRI over 8 years were retrospectively reviewed. The primary study outcome was the diagnostic accuracy of the 2 imaging modalities in detecting surgically treated spinal injuries.
Results:
The study population consisted of 100 patients. Computed tomography and magnetic resonance imaging demonstrated all 7 surgically treated injuries, although one of the injuries was initially missed with CT. Magnetic resonance imaging revealed more injuries, but none of the injuries visible on CT required surgical fixation. Magnetic resonance imaging was able to exclude unstable injuries in patients who had highly suspicious or unequivocal findings on CT.
Conclusions:
Magnetic resonance imaging and computed tomography were both highly accurate in detecting unstable pediatric spinal injuries requiring surgical treatment. Magnetic resonance imaging seems not to reveal additional unstable injuries after adequately interpreted spinal CT.
Level of Evidence:
Level III—retrospective observational study.